Tooth Discoloration after Regenerative Endodontic Procedures with Calcium Silicate-Based Cements—An Ex Vivo Study - Paulo J. Palma; Joana A. Marques; Joana Santos; Rui I. Falacho; Diana Sequeira; Patrícia Diogo; Francisco Caramelo; João C. Ramos; João Miguel Santos (Applied Sciences, 2020)
The aim of the present ex vivo study was to assess and compare coronal discoloration induced by four endodontic biomaterials used in regenerative endodontic procedures (REPs). Root resection was executed horizontally, 2 mm apical to the cementoenamel junction, in all fifty-four teeth. After accessing the pulp chamber, specimens were randomly divided in groups and filled with either saline solution or blood, followed by calcium silicate-based cements (CSCs) placement: ProRoot mineral trioxide aggregate (MTA) (Dentsply Sirona), Biodentine (Septodont), TotalFill BC (FKG), or pulp capping material (PCM) (Coltène). Color change (ΔE) was assessed using the L* a* b* system at five different timepoints (before and immediately after biomaterial application, 72 h, 7 days, and 6 months). The significance level for statistical analysis was set at p < 0.05. There are statistically significant differences regarding ΔE over time (p < 0.001). Statistical differences are found considering material (p < 0.001), treatment (p = 0.007), or both (p = 0.002). If solely the material or treatment is considered, regardless of time, statistically significant differences are detected (p < 0.001). After a six-month period of evaluation, blood exposure might be a critical factor in biomaterials’ color variation. Biodentine presents the lowest discoloration potential, followed by TotalFill and PCM, albeit without statistically significant differences. MTA exhibited the greatest color variation. The selection of biomaterial should consider the material’s discoloration potential.